Multimedia distribution, source apportionment, composition characteristics, and bioaccumulation effects of cyclic, linear, and modified methylsiloxanes in the Dongzhaigang mangrove ecosystem, Hainan Island, China - Wenming Chen; Hyo-Bang Moon; Xinrui Yang; Chuanbiao Xu; Jiliang Zhang; Xin Tian; Bowen Guan; Lin Wei (Environmental Research, 2026)

Identification of Novel Polysaccharide from Myxococcus xanthus and its Function in Developmental Sporulation - Lin Liu; Songchen Jiang; Guirong Yang; Wenming Chang; Jin Lin; Lujun Zhang; Yijia Xu; Xinyu Li; Jie Bai; Lei Zhang; Xianfeng Ye; Yan Huang; et al. (Current Microbiology, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Mechanisms underlying the modification of corn starch granules by raw starch-degrading amylase with substrate-targeting specificity - Lingli Zhong; Wenming Chang; Kai Yang; Songchen Jiang; Jin Lin; Yifei Shu; Yukun Zhong; Zehao Tang; Xianfeng Ye; Yanling Ji; Lei Zhang; Yan Huang; et al. (Carbohydrate Polymers, 2026)

Characteristics of phosphorus-solubilizing bacteria and mediated phosphorus cycle in sediments of urban river-lake interfaces - Yi Li; Xiaoxi Li; Lihua Niu; Jiaxin Hu; Wenlong Zhang; Li Lin; Wenming Zhang (Water Research, 2026)

An Integrated Stratigraphy Study of a Paralic Lacustrine Basin: Insights into the Organic Matter Accumulation - Meizhou Zhang; Xiaomin Zhu; Wenming Ji; Lei Ye; Xinping Zhou; Hongkui Chen; Xingyue Lin; Mianmo Meng (Journal of Marine Science and Engineering, 2026)
Several shale oil intervals, including those in offshore China, were deposited in paralic lacustrine basins that experienced marine incursions. Marine incursions could be either favorable or unfavorable for the accumulation of organic matter (OM) and shale oil. However, the influence and specific mechanisms of seawater on OM accumulation require further in-depth investigation. During the deposition of the Triassic Chang 7 Member in the Ordos Basin, seawater from the Paleo-Tethys Ocean intruded into the basin. Taking this interval as a case study, this paper employs comprehensive analyses to reveal the influence of marine incursion on water column conditions and OM accumulation. Under humid climatic conditions, the water body was fresh to brackish, characterized by high productivity and oxic–dysoxic conditions. The OM is primarily derived from algae, and its accumulation was jointly controlled by primary productivity, redox conditions, and terrigenous input. OM accumulation is controlled by fluctuations in the relative water level (RWL) associated with third-order sequences. During the period of high RWL, seawater incursions enhanced water column productivity and reduced conditions by increasing nutrient supply and salinity, resulting in the highest OM content. During the early and late periods of the RWL, as seawater receded, OM production declined while consumption and dilution increased, resulting in a gradual decrease in its content. The RWL fluctuations at the fourth-order scale also significantly influence OM accumulation. These results can enhance the understanding of OM accumulation in paralic lacustrine basins with a history of seawater incursion. While promoting shale oil exploration in the Ordos Basin, they can also serve as a research analog for shale oil exploration in basins with similar geological backgrounds, such as the Bohai Bay Basin.

Occurrence of beryllium and its microscale interactions with coexisting phases in beryllium-containing sludge - Xiaobo Min; Lin Yu; Yong Ke; Yunyan Wang; Wenming Zeng; Hui Xu; Yun Li; Cong Peng; Zhumei Sun (Journal of Environmental Sciences, 2026)

Bio-inspired coral-like ZnCo-LDH/Co-CAT hierarchical composite for multifunctional flexible pressure sensing and plantar monitoring system integration - Qingzheng Jia; Zelin Bai; Aijia Zhang; Zushan Huang; Wanxing Li; Ling Li; Youwei Zhao; Haijiao Lin; Wenming Zhang (Chemical Engineering Journal, 2026)

Hierarchical microstructure PANI@NH4V4O10@CC enables multifunctional pressure sensing and high capacity supercapacitive for self-powered wearable electronics - Yong Wang; Zelin Bai; Wanzhihan Zhang; Hang Li; Ling Li; Youwei Zhao; Haijiao Lin; Chuan Fang; Wenming Zhang (Chemical Engineering Journal, 2026)

Performance and mechanism study for 2-octanol oxidation by ozone in synergy with biochar supported manganese-based mullite catalysts - Lin Zhang; Huanzhen Zuo; Tong Wei; Wenming Pei; Xinsheng Zhu; Feng Ge; Kegui Zhang (Journal of Environmental Chemical Engineering, 2025)

Ferroptosis and iron metabolism drive fibroblast activation in silicosis: insights from a novel 3D lung matrix model - Chenzhao Song; Xinying Zeng; Jiaxin Wang; Wenming Xue; Yan Wang; Yifei Wang; Lin Tian; Zhonghui Zhu (Journal of Molecular Medicine, 2025)

High-entropy perovskite embedded in carbon-based catalyst toward peroxymonosulfate activation to degrade Rhodamine B: Performance and mechanism insights - Zihao Chen; Xingqi Huang; Yanjun Zuo; Haibo Wang; Wenming Chen; Lingce Kong; Xiaoyan Lin (Water Research, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Effects of plant species on reverse osmosis concentrate treatment in constructed wetlands: Performance, plant growth, and microbial community structure - Jie Wang; Tengfei Hu; Xiaohan Wei; Bin Xu; Xiaoyu Liu; Xiaoliang Zhai; Lin Chen; Wenxian Wang; Wenming Song; Shu Chen; Lihua Cheng; Xiaolin Zhou (Journal of Water Process Engineering, 2025)

Effect of Rice Straw Biochar on Rhizosphere Microbiome and Groundwater Quality During Phytoremediation of Alum Mines - Wenming Wang; Qilin Yu; Lin Zhao (Water, Air, & Soil Pollution, 2025)

Research on CO2 capture performance and reaction mechanism using a novel low energy consumption and high cyclic performance absorbent for onboard application - Yunlong Zhu; Hongyuan Xi; Song Zhou; Majed Shreka; Yifeng Wu; Jinquan Lin; Wenming Yang (Journal of Cleaner Production, 2024)

Flexible intelligent fabric composed of pinecone-like microstructure Co-cMOFs/CoZnAl-LDH composite nanomaterial for various types of sensor signals to guide personalized health activities - Aijia Zhang; Haijiao Lin; Tian Yuan; Qiancheng Zhu; Ling Li; Youwei Zhao; Wenming Zhang (Chemical Engineering Journal, 2024)

Integrated membrane process of tubular ultrafiltration-nanofiltration-electrodialysis-reverse osmosis for treating fracturing flowback fluid - Bing Xu; Qian Zhang; Huanhuan Wu; Qianqian Tian; Wenming Chai; Ming Zhang; Guangyi Shao; Shuwen Tian; Yakai Lin; Hong Yao (Journal of Cleaner Production, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

An improved wind quality control for the China-France Oceanography Satellite (CFOSAT) scatterometer - Xiaoheng Mou; Wenming Lin (Acta Oceanologica Sinica, 2024)

High arsenic pollution of the eutrophic Lake Taihu and its relationship with iron, manganese, and dissolved organic matter: High-resolution synchronous analysis - Wenming Yan; Xiangyu He; Musong Chen; Bao Qian; Minjuan Li; Yulin Yan; Chen Lin; Zhigang Mao (Journal of Hazardous Materials, 2024)

Joint Inversion of Sea Surface Wind and Current Velocity Based on Sentinel-1 Synthetic Aperture Radar Observations - Jingbei Sun; Huimin Li; Wenming Lin; Yijun He (Journal of Marine Science and Engineering, 2024)
Spaceborne synthetic aperture radar (SAR) has been proven to be a useful technique for observing the sea surface wind and current over the open ocean given its all-weather data-gathering capability and high spatial resolution. In addition to the commonly used radar return magnitude quantified by normalized radar cross section (NRCS), the Doppler centroid anomaly (DCA) has added another dimension of information. In this study, we combine the NRCS and DCA for a joint inversion of wind and surface current information using a Bayesian method. SAR-estimated Doppler is corrected by a series of steps, including the removal of scalloping effect and land correction. The cost function of this inversion scheme is constructed based on NRCS, DCA, and a background model wind. The retrieved wind results show the quality of performance through comparison with the in situ buoy measurements, showing a mean bias and a root-mean-square error (RMSE) of 0.33 m/s and 1.45 m/s for wind speed and 6.94° and 35.74° for wind direction, respectively. The correlation coefficients for wind speed and direction reach 0.931 and 0.661, respectively. Based on the obtained wind field, the line-of-sight velocity of the sea surface current is then derived by removing the wind contribution using the empirical model. The results show a consistent spatial pattern relative to the high-frequency radars, with the comparison relative to the drifter-measured current velocity exhibiting a mean bias of 0.02 m/s and RMSE of 0.32 m/s, demonstrating the reliability of the proposed inversion scheme. Such results will serve as a prototype for future spaceborne sensors to combine the radar return and Doppler information for the joint retrieval of wind vector and surface current velocity. This technique could be readily extended to the radar configuration of rotating beams for monitoring winds and current vectors.

Investigation of the mechanism of silica-induced pulmonary fibrosis: The role of lung microbiota dysbiosis and the LPS/TLR4 signaling pathway - Qiyue Jia; Hongwei Wang; Yan Wang; Wenming Xue; Qiyue Jiang; Jiaxin Wang; Fuao Ning; Zhonghui Zhu; Lin Tian (Science of The Total Environment, 2024)

Driving carbon emission reduction in China through green finance and green innovation: an endogenous growth perspective - Kunming Li; Weiyuan Lin; Tingjun Jiang; Yifan Mao; Wenming Shi (Environmental Science and Pollution Research, 2024)
Discovering drivers of carbon dioxide (CO 2 ) emissions is vital for the Chinese government to achieve carbon peak and carbon neutral. With this aim, a theoretical endogenous growth model capturing the mitigating effect of green finance and green innovation on carbon emissions is constructed in this study, which is further empirically examined using China’s municipal-level panel data during 2010–2019. The main findings are as follows: First, there is theoretical and empirical evidence supporting that green finance and green innovation can inhibit carbon emissions. Second, the above inhibitory effects demonstrate clear regional disparities with significant effects only in eastern and central Chinese cities, which are moderated by environmental regulations and marketization levels, respectively. Third, in cities with high green finance, green finance plays a more significant role in reducing carbon emissions than green innovation, and the opposite is true in cities with low green finance. In addition, the robustness and endogeneity checks indicate that the results of this study are robust and reliable. These theoretical and empirical findings create profound implications for CO 2 emission reduction by vigorously guiding funds to green finance and formulating scientific and effective environmental regulations to promote green innovation in China.

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

How does Microcystis aeruginosa respond to elevated temperature? - Yongqi Guo; Han Meng; Sichuan Zhao; Zixuan Wang; Lin Zhu; Dailan Deng; Jine Liu; Huan He; Wenming Xie; Guoxiang Wang; Limin Zhang (Science of The Total Environment, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

The impacts of assimilating CFOSAT scatterometer winds for Typhoon cases based on real-time rain quality control - Yaodeng Chen; Yemeng Cui; Wenming Lin; Jianqiang Liu; Congrong Sun; Shuyan Lang (Atmospheric Research, 2023)

A combined study on Vallisneria spiralis and lanthanum modified bentonite to immobilize arsenic in sediments - Wenming Yan; Xiangyu He; Tingfeng Wu; Musong Chen; Juan Lin; Xiang Chen; Qi Li; Minjuan Li; Yulin Yan; Qi Yao (Environmental Research, 2023)

Target controlled alternative hybridization chain reaction for fluorescent detection of dual mycotoxins - Qin Ma; Yiyan Lin; Yun Yang; Wenming Yang; Wen Yun; Mingming Zhang; Lizhu Yang (Analytica Chimica Acta, 2023)

Development of a dual-labeled, hydrolysis probe-based, real-time quantitative PCR assay for detection of both genotypes of duck circovirus-1 (DuCV-1) and DuCV-2 - Lin Zhang; Wenming Jiang; Fuyou Zhang; Yang Li; Jinping Li; Shaobo Liang; Xiaohui Yu; Cheng Peng; Shuo Liu; Jingjing Wang; Shuhong Sun; Hualei Liu (Virus Genes, 2021)

Residues and dissipation of trifloxystrobin and its metabolite in tomatoes and soil - Lin Wang; Wenming Li; Puyu Li; Minghui Li; Shuo Chen; Lijun Han (Environmental Monitoring and Assessment, 2014)

Characterisation of the subunit genes of pyrophosphate-dependent phosphofructokinase from loquat (Eriobotrya japonica Lindl.) - Qiaoping Qin; Quentin Kaas; Wenming Wu; Feifan Lin; Qixian Lai; Zhujun Zhu (Tree Genetics & Genomes, 2014)

A Prospective Evaluation of the Combined Helical Tomotherapy and Chemotherapy in Pediatric Patients with Unresectable Rhabdomyosarcoma of the Temporal Bone - Xinxin Zhang; Kun Ma; Jaling Wang; Wenming Wu; Lin Ma; Deliang Huang (Cell Biochemistry and Biophysics, 2014)

Design and optimization of a Ku-band rotating, range-gated fanbeam scatterometer - Wenming Lin; Xiaolong Dong (International Journal of Remote Sensing, 2011)